Explore Dubai - Klepeis, Alicia, 1971- (Great cities of the world (12 Story Library (Firm)), 2020)
Provides information about Dubai, United Arab Emirates, and its climate, history, economy, infrastructure, and culture. Features facts about Dubai's relationship with oil and expatriates. Includes color photographs, fact boxes, a map, a glossary, and resources for further learning.